2022
DOI: 10.1186/s12951-022-01550-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term maintenance of synaptic plasticity by Fullerenol Ameliorates lead-induced-impaired learning and memory in vivo

Abstract: Fullerenol, a functional and water-soluble fullerene derivative, plays an important role in antioxidant, antitumor and antivirus, implying its enormous potential in biomedical applications. However, the in vivo performance of fullerenol remains largely unclear. We aimed to investigate the effect of fullerenol (i.p., 5 mg/kg) on the impaired hippocampus in a rat model of lead exposure. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF–MS) is a kind of newly developed soft-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Fullerenol is a hydroxylated derivative of fullerene. Identical to previous studies ( Wang et al, 2016 ) ( Zha et al, 2022 ), the diameter of our aqueous fullerenol ranged from 100 to 1,000 nm. Notably, fullerenol was also manufactured to be nanomaterial with diameter lower than 100 nm ( Chen et al, 2022 ).…”
Section: Discussionsupporting
confidence: 81%
“…Fullerenol is a hydroxylated derivative of fullerene. Identical to previous studies ( Wang et al, 2016 ) ( Zha et al, 2022 ), the diameter of our aqueous fullerenol ranged from 100 to 1,000 nm. Notably, fullerenol was also manufactured to be nanomaterial with diameter lower than 100 nm ( Chen et al, 2022 ).…”
Section: Discussionsupporting
confidence: 81%
“…19,20 As a nanocomposite with promising applications, fullerenols are less harmful to living organisms and can cross the blood-brain barrier. 21,22 Additionally, fullerenols have a range of abilities, including anti-human immunodeficiency virus, antioxidant, anti-inflammatory, and neuroprotective properties. [23][24][25][26][27][28][29][30] Recent studies have revealed that fullerenols can restore normal dopaminergic neuron levels in the brain and reduce α-synuclein aggregation, which suggests that it could be neuroprotective agent for Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Water‐soluble polyhydroxylated fullerene derivatives, namely fullerenols, have a diameter of ≈1 nm with symmetrically arranged hydroxyl groups on C 60 spheres. [ 10 ] Stability for real‐time applications and intracellular localization [ 11 ] by directly crossing the cellular membrane [ 12 ] are prerequisites for fullerenols used in biomedical applications. Electron‐deficient carbon─carbon double bonds and hydroxyl groups can quench numerous electrophilic radicals; [ 13 ] this remarkable reaction to free radicals is the most important property of fullerenols.…”
Section: Introductionmentioning
confidence: 99%